RETRACTED: Management of current assets in the conditions of sustainable economic development - Klychova Guzaliya; Nizamutdinov Marat; Parfenova Kseniya; Oralbayeva Aizhan; Erkebulan Ydyrys; Mashayeva Ayagoz (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001